History education: Reaching beyond the confines of the classroom. A hands-on discussion of the implementation of rapidly improving technological tools in History pedagogy (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Since the dawn of the twenty-first century the technological tools at the disposal of teachers have improved exponentially. In the current education environment, the History teacher can reach far beyond the confines of a classroom, and is able to engage with the content of a study of human behaviour in a way that touches the humanity of students. A teacher in a single classroom can challenge students’ ability across an array of platforms and over an internet which both allows for the dissemination of ideas and the acquisition of information at a speed and with a reach heretofore unknown and unavailable to the pedagogue. In a rapidly changing and increasingly less predictable political, economic and cultural milieu, it is incumbent on the History specialist to instil in those who engage with the past, present and future, a humanity which transcends simplistic political demagoguery and narrow bigotry which is gaining traction internationally. The skills of discernment and thoughtful analysis of fact, opinion and belief that is the forte of an historian can counterbalance intolerance and a disturbing resurgence of inhumanity. The teaching of History can influence a generation to build a more caring and humane society and modern technology can enhance the ability of a teacher to engage with learners beyond the confines of their classroom.
Keywords: Technological tools; History pedagogy; Human behaviour; Humanity; Discernment; Counterbalance; Convergence